DEKADENSI MORAL: Integrasi Psikologi dan Teologi dalam Konseling Pastoral - Vebrianti Sari Patandean; Eka Grace Septiani, Jelyarvi Gusni, Estin Asri Kadang, Juwita Pratiwi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This study will analyze the eflectiveness of an integrative approach in pastoral counseling for addressing moral issues. This approach combines psychological, theological, and spiritual aspects, providing a comprehensive framework for understanding and addressing individual moral conflicts. The research finds that this integrative method allows counselors to ofler more holistic support by identifying the root causes of problems and providing deep, integrated solutions. Additionally, the study highlights the importance of integrity and honesty, as emphasized in Biblical teachings, in shaping individual moral and ethical character. These values help individuals remain steadfast in truth and make correct decisions despite temptations, while also supporting the creation of a just society consistent with moral principles upheld